Spontaneously Arising mutL Mutators in Evolving Escherichia coli Populations Are the Result of Changes in Repeat Length - Shaver, Aaron C. (American Society for Microbiology, 2003)
Over the course of thousands of generations of growth in a glucose-limited environment, 3 of 12 experimental populations of Escherichia coli spontaneously and independently evolved greatly increased mutation rates. In two of the populations, the mutations responsible for this increased mutation rate lie in the same region of the mismatch repair gene mutL. In this region, a 6-bp repeat is present in three copies in the gene of the wild-type ancestor of the experimental populations but is present in four copies in one of the experimental populations and two copies in the other. These in-frame mutations either add or delete the amino acid sequence LA in the MutL protein. We determined that the replacement of the wild-type sequence with either of these mutations was sufficient to increase the mutation rate of the wild-type strain to a level comparable to that of the mutator strains. Complementation of strains bearing the mutator mutations with wild-type copies of either mutL or the mismatch repair gene uvrD rescued the wild-type mutation rate. The position of the mutator mutations—in the region of MutL known as the ATP lid—suggests a possible deficiency in MutL's ATPase activity as the cause of the mutator phenotype. The similarity of the two mutator mutations (despite the independent evolutionary histories of the populations that gave rise to them) leads to a discussion of the potential adaptive role of DNA repeats.